METHODOLOGICAL FOUNDATIONS OF PLANNING AND EVALUATING FIELD TRAINING - Odiljon Tobirov; Xidoyatkhon Abdinazarova; Azamjon Jobborov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the methodological foundations of planning and evaluating field training, emphasizing the role of structured frameworks in enhancing training effectiveness and accountability. Drawing on established evaluation models and contemporary methodological approaches, the study examines key stages of field training design, including objective setting, data collection, monitoring, and outcome assessment. Special attention is given to the integration of qualitative and quantitative evaluation tools, such as pre- and post-training assessments, performance-based metrics, and feedback mechanisms, which together provide a comprehensive understanding of training impacts. The analysis highlights the importance of iterative evaluation and evidence-based decision-making in improving professional competencies and practical readiness. The findings suggest that adopting systematic, adaptable, and data-driven methodologies significantly strengthens the quality and sustainability of field training programs, supporting continuous improvement and informed management practices.